Myocardial infarction among Danish HIV-infected individuals: population-attributable fractions associated with smoking - Rasmussen, Line D; Helleberg, Marie; May, Margaret T; Afzal, Shoaib; Kronborg, Gitte; Larsen, Carsten S; Pedersen, Court; Gerstoft, Jan; Nordestgaard, Børge G; Obel, Niels (Clinical infectious diseases, 2015)
Human immunodeficiency virus-infected individuals have increased risk of myocardial infarction (MI); however, the contribution from smoking and potentiating effects of HIV are controversial. From the Danish HIV Cohort Study and the Copenhagen General Population Study, we identified 3251 HIV-infected individuals and 13 004 population controls matched on age and gender. Data on MI were obtained from the National Hospital Registry and the National Registry of Causes of Death. We calculated adjusted incidence rate ratios (aIRR) for risk of MI and population-attributable fractions (PAF) of MI associated with smoking. In never smokers, HIV was not associated with an increased risk of MI (aIRR, 1.01; 95% confidence interval [CI], .41-2.54). In previous and current smokers, HIV was associated with a substantially increased risk of MI (aIRR, 1.78; 95% CI, .75-4.24 and aIRR, 2.83; 95% CI, 1.71-4.70). The PAF associated with ever smoking (previous or current) was 72% (95% CI, 55%-82%) for HIV-infected individuals and 24% (95% CI, 3%-40%) for population controls. If all current smokers stopped smoking, 42% (95% CI, 21%-57%) and 21% (95% CI, 12%-28%) of all MIs could potentially be avoided in these 2 populations. Smoking is associated with a higher risk of MI in the HIV-infected population than in the general population. Approximately 3 of 4 MIs among HIV-infected individuals are associated with ever smoking compared with only 1 of 4 MIs among population controls. Smoking cessation could potentially prevent more than 40% of MIs among HIV-infected individuals, and smoking cessation should be a primary focus in modern HIV care.